COGNITIVE AND METACOGNITIVE STRATEGIES IN ARABIC LISTENING LEARNING AND RELATIONSHIP WITH STUDENTS’ PERSONALITY - Barnabas, Raden Ahmad; Rafli, Zainal; Rasyid, Yumna (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
The purpose of this study was to find the effect of learning strategies (metacognitive and cognitive strategies) and personality (intrinsic and extrinsic personality) on Arabic listening skills. It was experiment research with experimental methods by factorial 2x2 design. It used a 2-way analysis variance design. The process of collecting data used questionnaires, tests, observations, and documentation. The results showed that there was a significant influence on Arabic listening ability with different personality levels. Personality differences in the application of listening learning strategies are closely related. Language learning varies depending on individual characteristics and variations in language learning outcomes associated with student characteristics. Cognitive and metacognitive strategies have a significant influence on the Arabic listening ability with different levels of personality types namely extrovert and introvert. Therefore, it can be concluded that different personalities will influence the level of different listening skills in Arabic. The results of the study recommend that the learning process of listening to Arabic using metacognitive and cognitive strategies can be varied with the concept of group learning and enrichment of vocabulary from the material presented.